Evaluación de dos niveles de fertilización mas dos tipos de tutoreo y tres dosis de etephon para igualar la maduración de la semilla de alfalfa ( medicago sativa l.) en la localidad ubicada en la parroquia Eloy Alfaro barrio Sarapamba – Cotopaxi - Chariguamán Galarza, Eliana Azucena (2014)
The research was, "Evaluation of two fertilization levels plus two tutoring systems and three doses of ethephon to meet maturing seed alfalfa (Medicago sativa L.)". It was held on the property of Mrs. Delfina Caiza that is located in Cotopaxi province, Latacunga Canton, Eloy Alfaro Parish, Sarapamba neighborhood. The specific objectives were to evaluate and select the best dose of ethephon to match the maturity of the alfalfa seed and perform economic analysis of treatments. Three factors were set: fertilization levels: n1: 120-160-190 and n2: 140-180-210; tutoring systems: t1: trellis, t2: traditional; and dose Ethefhon: d1: 0.5 cc / l, d2: 1.0 cc / l d3: 1.5 cc / l. Design Randomized Complete Block (RCBD) 2x2 and 2x2x3 +1 +1, with three repetitions and an absolute control was performed. For sources of significant variation Tukey test at 5% and the Least Significant Difference (LSD) at 5% was applied. The economic analysis was performed using the cost / benefit calculation. According to the results obtained for plant height, the best fertilization was level n2: 140-180-210 with 40.50, 78.29 and 92.54 cm at 30, 60 and 90 days, tutored t1: 41 trellis , 24: 79.38, 94.27 cm at 30, 60, and 90 days….